2-Deoxy adenosine triphosphate improves contraction in human end-stage heart failure. (February 2015) - Moussavi-Harami, Farid; Razumova, Maria V.; Racca, Alice W.; Cheng, Yuanhua; Stempien-Otero, April; Regnier, Michael
Abstract: We are developing a novel treatment for heart failure by increasing myocardial 2 deoxy-ATP (dATP). Our studies in rodent models have shown that substitution of dATP for adenosine triphosphate (ATP) as the energy substrate in vitro or elevation of dATP in vivo increases myocardial contraction and that small increases in the native dATP pool of heart muscle are sufficient to improve cardiac function. Here we report, for the first time, the effect of dATP on human adult cardiac muscle contraction. We measured the contractile properties of chemically-demembranated multicellular ventricular wall preparations and isolated myofibrils from human subjects with end-stage heart failure. Isometric force was increased at both saturating and physiologic Ca 2 + concentrations with dATP compared to ATP. This resulted in an increase in the Ca 2 + sensitivity of force (pCa50 ) by 0.06 pCa units. The rate of force redevelopment (ktr ) in demembranated wall muscle was also increased, as was the rate of contractile activation ( k ACT ) in isolated myofibrils, indicating increased cross-bridge binding and cycling compared with ATP in failing human myocardium. These data suggest that dATP could increase dP/dT and end systolic pressure in failing human myocardium. Importantly, even though the magnitude and rate of force development were increased, there was no increase in the time to 50% and 90% myofibril relaxation. These data, along with our previous studies in rodent models, show the promise of elevating myocardial dATP to enhance contraction and restore cardiac pump function. These data also support further pre-clinical evaluation of this new approach for treating heart failure. Highlights: Contraction in human heart failure sample was measured in the presence of ATP or dATP. dATP increases isometric force and Ca 2 + sensitivity in demembranated samples. dATP increases rate of force redevelopment in demembranated samples. 10% dATP substitution significantly increases isometric force. dATP increases rate of myofibril activation without altering relaxation kinetics.